2008
DOI: 10.1084/jem.20080281
|View full text |Cite
|
Sign up to set email alerts
|

Immune-driven recombination and loss of control after HIV superinfection

Abstract: After acute HIV infection, CD8 + T cells are able to control viral replication to a set point. This control is often lost after superinfection, although the mechanism behind this remains unclear. In this study, we illustrate in an HLA-B27 + subject that loss of viral control after HIV superinfection coincides with rapid recombination events within two narrow regions of Gag and Env. Screening for CD8 + T cell responses revealed that each of these recombination sites ( ‫ف‬ 50 aa) encompassed distinct regions con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
123
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 29 publications
8
123
0
4
Order By: Relevance
“…2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant. Others have reported dual infection 10 or superinfection 3,5,6 with the same subtype followed by recombination. Koelsch et al 11 described complete replacement of drug-resistant virus with superinfecting wild-type virus, while Pingen et al 12 described complete replacement of wildtype virus with drug-resistant virus, but recombination was not detected in these reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant. Others have reported dual infection 10 or superinfection 3,5,6 with the same subtype followed by recombination. Koelsch et al 11 described complete replacement of drug-resistant virus with superinfecting wild-type virus, while Pingen et al 12 described complete replacement of wildtype virus with drug-resistant virus, but recombination was not detected in these reports.…”
mentioning
confidence: 99%
“…However, superinfection may be difficult to detect when the superinfecting virus is of the same subtype as the initial virus, and the detection of possible consequent recombinants is restricted to a handful of reports. [2][3][4][5][6] It has previously been reported that superinfection with a virus of different subtype can result in replacement of the original virus. 2,7-9 Fang et al 4 showed replacement of subtype A virus with AC, but did not show the presence of ''pure'' subtype C virus, so the superinfection could have been with an AC recombinant.…”
mentioning
confidence: 99%
“…While the neutralizing antibody response was found to be low, a cellular response of this magnitude and breath did not translate into protection against the second HIV-1 strain even though its sequence only differed by 12%. Thus, these and additional well-documented cases demonstrated that superinfection can occur in the context of limited HIV-1-specific cytotoxic T cell responses mostly directed against a single epitope [10,35], yet it is not prevented by the presence of broad responses to multiple epitopes [9,11,34,39].…”
Section: Role Of T Cell Responses In Hiv-1 Superinfectionmentioning
confidence: 99%
“…For instance, rapid generation of recombinant strains following HIV-1 superinfection might significantly enhance the ability of the newly produced virus to evade the immune system in controllers. Indeed, recombination events between the initial and the superinfecting HIV-1 strains within crucial regions targeted by HIV-1-specific CD8+ T cells led to viral escape and disease progression in one individual carrying the protective HLA-B27 allele [35].…”
Section: Impact Of Hiv-1 Superinfection On the Spontaneous Control Ofmentioning
confidence: 99%
See 1 more Smart Citation